D‐A type hybrid polymers based on EDOT and various benzodiazoles for electrochromic materials. Issue 36 (14th May 2021) - Xu, Haoran; Hou, Yanjun; Li, Rui; Chang, Lijing; Ma, Yang; Miao, Shoulei; Niu, Haijun
Abstract: Two donor units (D)‐acceptor units (A) type monomers were synthesized by Stille coupling reaction, and then three D‐A type hybrid polymers based on 3, 4‐ethylenedioxythiophene and various benzodiazoles were synthesized by electrochemical polymerization. Spectroelectrochemical and kinetic studies of these polymers showed that all polymer films exhibited excellent electrochromic behavior, obvious optical contrast, and excellent stability. Among them, the response time of P3 film was the shortest ( t c  = 1.6 s, t b  = 2.2 s), the coloring efficiency of P2 film was the highest ( CE  = 333 cm 2 ·C −1 ), and the stability of P1 was the best (the ΔT loss of P1 after 1000 s cycles is only 2.3%). Therefore, these data prove that these new polymers have great potential in applications as electrochromic materials. Abstract :